Impacts of import refusals on agricultural exports during pandemics: Implications for China - Mao, Rui; Jia, Ziyi; Chen, Kevin Z. (John Wiley & Sons, 2021)
Pandemic outbreaks disrupt agricultural trade. The possible strengthening of import barriers to products from countries at the epicenter of a pandemic by their trade partners could aggravate this situation. This paper examines the responses of the US Food and Drug Administration (FDA), import refusals, and subsequent trade impacts on the agricultural exports from the developing countries that were the epicenters of four pandemics in the past two decades. Using monthly data for the period 2002–2020, we find increased import refusals and amplified trade‐impeding impacts on agricultural exports during pandemic outbreaks. Increased import refusals and the amplification of the trade‐impeding effect of import refusals were especially large when China was the epicenter. We further examine possible differences in these results across products and FDA inspection methods, and the main conclusions remain robust. This paper offers a better understanding of the economic outcomes of pandemic outbreaks and provides policy suggestions for China.